Eco-Friendly Management of Root-knot Nematode Meloidogyne incognita (Kofid and White) Chitwood Using Different Green Leaf Manures on Tomato under Field Conditions - Pakeerathan, K.; Mikunthan, G.; Tharshani, N. (IDOSI Publications, 2009)
A field study was conducted to test the effect of different green leaf manures elucidate as eco-friendly management of M.incognita on tomato. Recommended dosage of green leaf manures, such as Gliricidia maculata, Thespesia populnea, Calotropis gigantia, Azadiracta indica and Glycosmis pentaphylla were compared with control as treatments. The results revealed that extent of galling (35.87), gall index (0.327), yield (17.87 Mt/ha), Reproductive factor (0.411) and plant growth includes height and dry matter, respectively (22.47 cm and 45.08 g) were significantly best in Gliricidia maculata compared to other treatments. While other green leaf manures, T. populnea and A. indica ranked second and third, respectively in managing M. incognita. This study also revealed that green leaf manures improve the plant growth and reduced the nematode infestation in tomato fields. Moreover, G. maculata can be used as an alternative in eco-friendly manage root-knot nematode
Keywords: Gliricidia Maculate; Meloidogyne Incognita; Tomato Root-knot; Greenleaf Manures